Semarak Perkembangan dan Pertunjukan Tambua Tasa di Tengah Kehidupan Sosiokultural Masyarakat Selingkar Danau Maninjau - Wardizal Wardizal (Journal of Music Science, Technology, and Industry, 2022)
Purpose: Tambua Tasa is a form of traditional music that grows and develops in Minangkabau, especially the people around Lake Maninjau, Agam Regency, West Sumatra. Substantively, what I want to put forward in this paper is a narrative about the splendor of the Tambua performance in the midst of the socio-cultural life of the community, both in the context of traditional ceremonies and socially. Research Methods: The data in this paper are based on the results of observations, interviews, document studies from print and electronic media information (google, you tube and FB) which are analyzed in depth to obtain reliable information. Results and Discussion: Tambua Tasa has experienced very rapid development amidst the socio-cultural life of the people around Lake Maninjau, West Sumatra. Tambua tasa, which in the past only developed and belonged to the village, has now expanded into the world of education, starting from the elementary school level to the high school level. Implication: The transfer of generations from traditional music is also going very well with the emergence of young talents full of talent.